Control of bifurcation by fuzzy logic controller for current-mode boost converters - Khaehintung, Noppadol; Sirisuk, Phaophak; Kunakorn, Anantawat (My University, 2007)
This paper presents the design of a fuzzy logic controller for switching current-mode DC/DC boost converters. The proposed simple fuzzy logic controller, with nine rules, provides an optimal slope compensation to keep the system adequately remote from the first bifurcation point by means of reducing the current spectrum peak. In spite of nonlinear characteristics and instabilities of the converter, the performance of the closed-loop control system can be considerably improved to avoid bifurcation phenomena. It is found that the technique introduced in this paper gives satisfactory results with the regulating and tracking modes under changes in operating conditions. © 2006 IEEE.
Keywords: A current-mode boost converter; Bifurcation phenomena; Fuzzy logic controller; Slope compensation